A case–control analysis of smoking and breast cancer in African American women: findings from the AMBER Consortium. (7th April 2016) - Park, Song-Yi; Palmer, Julie R.; Rosenberg, Lynn; Haiman, Christopher A.; Bandera, Elisa V.; Bethea, Traci N.; Troester, Melissa A.; Viscidi, Emma; Kolonel, Laurence N.; Olshan, Andrew F.; Ambrosone, Christine B.
Summary: In African American women, we found an increased risk of postmenopausal breast cancer associated with long duration and greater pack-years of smoking, possibly stronger for ER+ cancer, but a decreased risk of premenopausal breast cancer in former and current smokers. Abstract: Recent population studies suggest a role of smoking in the etiology of breast cancer, but few have been conducted among African American women. In a collaborative project of four large studies, we examined associations between smoking measures and breast cancer risk by menopause and hormone receptor status [estrogen receptor-positive (ER+), ER-negative (ER−) and triple-negative (ER−, PR−, HER2−)]. The study included 5791 African American women with breast cancer and 17376 African American controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated in multivariable logistic regression analysis with adjustment for study and risk factors. Results differed by menopausal status. Among postmenopausal women, positive associations were observed for long duration and greater pack-years of smoking: relative to never smoking, fully adjusted ORs were 1.14 (95% CI: 1.03–1.26) for duration ≥20 years and 1.16 (95% CI: 1.01–1.33) for ≥20 pack-years. By contrast, inverse associations were observed among premenopausal women, with ORs of 0.80 (95% CI: 0.68–95) for current smoking and 0.81 (95% CI: 0.69–0.96) for former smoking, without trends by duration. Associations among postmenopausal women were somewhat stronger for ER+ breast cancer. The findings suggest that the relation of cigarette smoking to breast cancer risk in African American women may vary by menopausal status and breast cancer subtype.